2007
DOI: 10.1111/j.1462-2920.2007.01282.x
|View full text |Cite
|
Sign up to set email alerts
|

Isotope analysis as a natural reaction probe to determine mechanisms of biodegradation of 1,2‐dichloroethane

Abstract: 1,2-Dichloroethane (1,2-DCA), a chlorinated aliphatic hydrocarbon, is a well-known groundwater contaminant. In this study, fractionation of stable carbon isotope values of 1,2-DCA during biodegradation was used as a novel reaction probe to provide information about the mechanism of 1,2-DCA biodegradation under both aerobic (O2-reducing) and anaerobic (NO3-reducing) conditions. Under O2-reducing conditions, an isotopic enrichment value (epsilon) of -25.8 +/- 1.1 per thousand (+/-95% confidence intervals) was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 31 publications
(70 reference statements)
2
23
0
Order By: Relevance
“…This conclusion is in agreement with the Streitwieser limit for 13 C-KIE in C−Cl bonds (1.057) 44 and could explain in part the relatively narrow range of reported ε bulk C values (from −28.7 to −33.0‰) for both pure cultures using the haloalkane hydrolytic dehalogenase reaction ( Table 2). Hirschorn et al 9 measured a similar 13 C-AKIE (1.05) for 1,2-DCA in laboratory biodegradation experiments under nitrate reducing conditions by an enrichment culture from a contaminated site, which was interpreted as transformation via hydrolytic dehalogenation.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…This conclusion is in agreement with the Streitwieser limit for 13 C-KIE in C−Cl bonds (1.057) 44 and could explain in part the relatively narrow range of reported ε bulk C values (from −28.7 to −33.0‰) for both pure cultures using the haloalkane hydrolytic dehalogenase reaction ( Table 2). Hirschorn et al 9 measured a similar 13 C-AKIE (1.05) for 1,2-DCA in laboratory biodegradation experiments under nitrate reducing conditions by an enrichment culture from a contaminated site, which was interpreted as transformation via hydrolytic dehalogenation.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Stable isotope fractionation (i.e., a change in the 13 C/ 12 C ratio) during biodegradation occurs due to differences in the reaction rates and activation energies of heavy and light atoms present at a reacting bond, with lightisotope bonds in general reacting more quickly (16,46). The degree of fractionation depends strongly on the type of bond being cleaved and, therefore, the mechanism of the initial step in degradation (5,11,24,25). During biodegradation of many chlorinated ethenes and chlorinated ethanes, it has been found that the preferential breakage of the bond containing the lighter isotope (resulting in enrichment of the heavy isotope in the remaining substrate) can be described by the Rayleigh equation (4,25,27,53,57):…”
Section: Methodsmentioning
confidence: 99%
“…14,25 The analysis was confirmed by carbon isotope fractionation measurements with pure strains of known transformation mechanisms, 72 and was subsequently used to probe for the mechanism under nitrate-reducing conditions. 73 Through a careful analysis in terms of position-specific isotope effects, the binomial distribution of enrichment factors could therefore be linked to different underlying transformation mechanisms! Almost simultaneously, the same approach made it possible to infer for the first time the transformation mechanism of anaerobic methyl tert-butyl ether (MTBE) degradation.…”
Section: Deriving Transformation Mechanisms From Isotope Fractionationmentioning
confidence: 99%